MLTSP - Willingness to vaccinate and willingness to pay for vaccination against PPR - Wane, Abdrahmane; Fall, Abdou; Dione, Michel; Rich, Karl (2023)
Feed the Future Mali Livestock Technology Scaling Program or FTF-MLTSP, Analysis of the socio-economic factors influencing farmer willingness to vaccinate and willingness to pay for vaccination during and in the absence of vaccination campaigns.